2020
DOI: 10.3762/bjnano.11.3
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the drag reduction performance of bioinspired pipeline surfaces with transverse microgrooves

Abstract: A novel surface morphology for pipelines using transverse microgrooves was proposed in order to reduce the pressure loss of fluid transport. Numerical simulation and experimental research efforts were undertaken to evaluate the drag reduction performance of these bionic pipelines. It was found that the vortex ‘cushioning’ and ‘driving’ effects produced by the vortexes in the microgrooves were the main reason for obtaining a drag reduction effect. The shear stress of the microgrooved surface was reduced signifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Implicit Equation ( 18) is solved by the dichotomy to obtain η ν . In Figure 16, we compare the prediction of Equation (18) with CFD data in the present, The CFD data reported by Wu et al (2019) [5], and the experimental data reported by Liu et al (2020) [32]. The reason why the relationship between η ν and U + ∞ is used, η ν U + s , is shown in Figure 16 and is mainly to facilitate the comparison between the results predicted by Equation ( 18) and the data obtained by previous studies.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Implicit Equation ( 18) is solved by the dichotomy to obtain η ν . In Figure 16, we compare the prediction of Equation (18) with CFD data in the present, The CFD data reported by Wu et al (2019) [5], and the experimental data reported by Liu et al (2020) [32]. The reason why the relationship between η ν and U + ∞ is used, η ν U + s , is shown in Figure 16 and is mainly to facilitate the comparison between the results predicted by Equation ( 18) and the data obtained by previous studies.…”
mentioning
confidence: 83%
“…The inconsistency of the application object may have been the reason for the minor errors. Meanwhile, the optimal dimensionless groove depth for pipelines, H + opt = 8.488, was observed by the water tunnel experiment of Liu et al [32] with a Reynolds number of 50,000 (U + ∞ = 17.326). In this case, the optimal dimensionless groove depth predicted by the model is 9.215, and the relative error between the model results and the experimental results is 7.8%, which qualitatively proves the correctness of the model.…”
Section: Verification Of the Quasi-analytical Solutionmentioning
confidence: 94%
See 3 more Smart Citations